Outdoor Performance Assessment of New and Old Photovoltaic Panel Technologies Using a Designed Multi-Photovoltaic Panel Power Measurement System - Mehmet Karabulut; Huseyin Kusetogullari; Sinan Kivrak (International Journal of Photoenergy)
This paper presents a new multi-photovoltaic panel measurement and analysis system (PPMAS) developed for measurement of atmospheric parameters and generated power of photovoltaic (PV) panels. Designed system presented with an experimental study evaluates performance of four new and four 5-year-old PV panel technologies which are based on polycrystalline (Poly), monocrystalline (Mono), copper indium selenide (CIS), and cadmium telluride (CdTe) in real time, under same atmospheric conditions. The PPMAS system with the PV panels is installed in Yildirim Beyazit University, Ankara Province, in Turkey. The designed PPMAS consists of three different subsystems which are (1) photovoltaic panel measurement subsystem (PPMS), (2) meteorology measurement subsystem (MMS), and (3) data acquisition subsystem (DAS). PPMS is used to measure the power generation for PV panels. MMS involves different types of sensors, and it is designed to determine atmospheric conditions including wind speed, wind direction, outdoor temperature, humidity, ambient light, and panel temperatures. The measured values by PPMS and MMS are stored in a database using DAS subsystem. In order to improve the measurement accuracy, PPMS and MMS are calibrated. This study also focuses on outdoor testing performances of four new and four 5-year-old PV panels. Average monthly panel efficiencies are estimated as 8.46%, 8.11%, 5.65%, and 3.88% for new Mono, new Poly, new CIS, and new CdTe PV panels, respectively. Moreover, average monthly panel efficiencies of old panels are calculated as 8.22%, 7.85%, 5.35%, and 3.63% in the same order. Test results obtained from the experimental system are also statistically examined and discussed to analyze the performance of PV panels in terms of monthly panel efficiencies.